(untitled) (Studia Prawnicze / The Legal Studies, 1964)
In the development of the organization and the functioning of the administration of economic relations there can be pointed out, in essence, three fundamental periods: a) years following the constitution of People’s Poland (1944) till the end of the year 1949, characterized by the rebuilding of devastations caused by the war and the organization of a system of planned economy; b) years of an intensive industrialization; c) the period after 1956 — period of framing and realization of a new pattern of the economic administration, based on the system of planned economy and of a decentralized operative carrying out of plans. The starting point, of social reforms in Poland after the year 1944 was the taking over of the power by new political authorities representing the interests of the working masses. During the first years after the liberation the agricultural reform and the nationalization of the big and medium industry had been carried out. The system of organs of economic administration was based in the beginning on structural patterns of the pre-war period. With the growth of state enterprises these forms proved insufficient. In the beginning of the year 1947 there had been issued a decree with the validity of law which established the legal status of state enterprises and their superior organs. It was during this period that several fundamental acts establishing the principles of a planned economy had been issued, namely: the decree with the validity of law on the planned national economy, the decree with the validity of law on the state investment plan and the decree with the validity of law on the planned space economic management of the country. There had been created a chief organ in the field of planning — the Central Planning Office. In the year 1948 the political and state management have formulated more complete principles of the economic planing, based on the intergrity and the dynamics of planning. Years 1950 — 1955 are years of an intensive industrialization. This tremendous effort demanded a centralization of the essential economic decisions and an uniform management of the economic administration. These requirements caused a notable development of the number of head organs of the state as well as several changes in the methods of planning and of administration. In place of the abolished Central Planning Office a State Commission of Economic Planning has been instituted; besides the planning tasks, the above mentioned Commission was invested with many rights of direct management. New ministeries invested with the management of the activity of subordinated enterprises has been instituted. Economic plants determined thoroughly the economic tasks of state enterprises. By virtue of the law of March 20th, 1950 a fundamental reform of the system of local organs was carried out. Organs of governmental and self-governmental administration had been abolished and their activities had been taken over by national councils. This reform had created favourable conditions for the development of local planning, based on the system of national councils. In 1950 rules concerning state enterprises had also undergone a change. A decree with the validity of law determined the legal status of enterprises, the way of organizing them, organs of enterprises and their supervision. There had been also issued several legal acts in order to regulate various spheres of the economic activity of the state. As result of the intensive industrialization was an excessive centralization of the administration of the national economy. The process of decentralization begins after 1956. It is characterized by the transfer of many tasks to the local units. It ,is followed by the reduction of the number of ministries and by the change of the part played by the planning organs which begin to deal with the directions of the economic development and the correlation of various fields of economy. The Council of Ministers concentrates attributions of a general management and of determination of conditions of the functionning of the national economy. The situation of an enterprise is undergoing an essential change. The enterprise is endowed with the right to establish its planning tasks and to determine the economic connections with other enterprises. In many enterprises there are constituted organs of worker self-government, participating in the process of the management of enterprises. The workers are economically interested in profits as they have a share in the part of these profits. The superior units undergo equally a transformation. There are constituted unions of state enterprises endowed with legal personality chiefly aiming at the coordination of the activities of enterprises of the same profile of production, at the assistance in their activity, at the care of their technical progress and s. o. Organs of the union are: the manager and the board composed of managers of enterprises members of the union. VIII. The growth of the independence of state enterprises and the decentralization in the system of the administration of the national economy emphasize the importance of the co-ordination of various enterprises and branches of production. The forms of coordination practiced hitherto, that is — the horizontal co-ordination and the vertical co-ordination — prove insufficient. There appear new forms, namely the so called branch co-ordination and the co-ordination done by national councils. The branch co-ordination comprises the co-ordination of the enterprises belonging to different organizations realizing some common economic tasks. The coordination done by national councils (mainly Voivodships councils) comprises the co-operation of units situated on the territory of a given unit of the administrative division. These new coordination-combinations require new legal forms. Consequently there is developed an intensive activity in order to systematize legal rules and create new legal institutions answering the purposes of these tasks.